2020
DOI: 10.3389/fpls.2019.01744
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Distribution of Erucic Acid in Brassica napus Seeds

Abstract: Brassica napus (B. napus) is the world's most widely grown temperate oilseed crop. Although breeding for human consumption has led to removal of erucic acid from refined canola oils, there is renewed interest in the industrial uses of erucic acid derived from B. napus, and there is a rich germplasm available for use. Here, low-and high-erucic acid accessions of B. napus seeds were examined for the distribution of erucic acid-containing lipids and the gene transcripts encoding the enzymes involved in pathways f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…In this study, we imaged labeled molecular species of PC because it is an intermediate for TG synthesis within embryonic development, as well as an important membrane lipid, and it is well suited for MS imaging. Additionally, many other MS imaging studies have found different PC molecular species, varying in their fatty acid composition, are heterogeneously distributed among seed tissues, suggesting a difference in metabolism that may be revealed through isotopic labeling imaging [ 23 , 24 , 25 , 26 , 27 , 28 ]. Hence, imaging the molecular species of PC demonstrates the potential value of 13 C-MSI for lipid metabolism studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we imaged labeled molecular species of PC because it is an intermediate for TG synthesis within embryonic development, as well as an important membrane lipid, and it is well suited for MS imaging. Additionally, many other MS imaging studies have found different PC molecular species, varying in their fatty acid composition, are heterogeneously distributed among seed tissues, suggesting a difference in metabolism that may be revealed through isotopic labeling imaging [ 23 , 24 , 25 , 26 , 27 , 28 ]. Hence, imaging the molecular species of PC demonstrates the potential value of 13 C-MSI for lipid metabolism studies.…”
Section: Resultsmentioning
confidence: 99%
“…While such conclusions require further evidence, including analysis of mutants in PC and TAG biosynthesis, HPLC-MS/MS of extracts from dissected embryonic tissues and MS/MS analysis of labeled metabolites to determine what parts of PC have been labeled, here we demonstrate that combining isotopic labeling of lipids and MSI is able to provide new information about tissue-specific differences in metabolism that would otherwise remain hidden in typical extraction-based methods. Such examination of these metabolic differences will help to provide explanations for the heterogeneity of metabolites observed within different tissues, and will continue to uncover the complex spatial dimension to metabolism [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC is an important structural membrane lipid in seeds and is also an intermediate in the biosynthesis of TAG. Given that different molecular species of PC and TAG have been found to be distributed in an unequal manner in seed tissues of many plant species (Marmon et al, 2017;Woodfield et al, 2017;Lu et al, 2018Lu et al, , 2020Sturtevant et al, 2019), it was not clear how the mutant genotypes generated here would influence those normal distributions. MALDI-MS imaging allows for a comprehensive view of the lipid metabolites distributed in seed sections.…”
Section: Visualizing Heterogeneous Distributions Of Pc and Tag In Pennycress Mutant And Wild-type Seeds Via Maldi-msimentioning
confidence: 97%
“…Like PC, different TAG molecular species of oilseeds have previously been observed to localize preferentially to different seed tissues (Marmon et al, 2017;Woodfield et al, 2017;Lu et al, 2018Lu et al, , 2020Sturtevant et al, 2019). In wild-type seeds, the most abundant TAG molecular species were the erucic acid-containing TAG-62:4, 62:5 (Figure 6) and TAG-60:4, 60:5 (Supplementary Figure 8), preferentially localized to the cotyledons, while the embryonic axis showed a relative enrichment in 52 and 54 carbon TAG species (Supplementary Figure 8 and Figure 6).…”
Section: Heterogeneous Distributions Of Pc and Tag In Mutant And Wild-type Seedsmentioning
confidence: 99%